(untitled) (LIS TODAY, 2023)
The aim of this research is to see the PICO and its implication for the medical library with special reference to Government Medical College Kota. A medical library is a kind of library purposely designed to assist medical doctors, physicians, and other related medical practitioners, who practice medicine whose concerned with promoting and maintaining health through the diagnosis study, of a recipient of health care service performed by a healthcare professional, PICO is the process of finding the appropriate response to the debt that arises in patient care depends on how we structure the relevant of these methods. The author will look at its implication in medical libraries, present, and future, Moreso, medical libraries will be vividly defined, and there used the PICO framework patient or problem, intervention or issues, and the outcome will also further explain, the challenges of the patient or problem, intervention or issues, and the outcome (PICO) in medical libraries to the medical practitioner’s preferred solution to the medical practitioners. Recommendation of the discussion and final conclusion of the study and reference.